What would you like to do?

# What is -5c plus 9 and how?

# 5c plus 7-3 plus 2c?

7c+4

# 3c-12 equals 14 plus 5c?

3c - 12 = 14 + 5c Subtract 3c from each side: -12 = 14 + 2c Subtract 14 from each side: -26 = 2c Divide each side by 2: -13 = c

# What is 5c plus 15 equals 30?

5c + 15= 30 - 15 -15 5c = 15 If your solving for just c..... 5c/5 = 30/5 c= 3 Hope this helps adding further your question is incomplete you must ask for thevalue of C, s…ince its a arithmetic equation.

# How do you simplify 4c2 plus 5c plus 2c?

4c 2 + 5c + 2c = 4c 2 + 7c = c(4c + 7)

# What are the 5Cs?

If you mean the 5 C's, like you learn in school and such, it's Cotton Citrus Copper Climate Cattle

# What is the answer to 20c plus 5 equals 5c plus 65?

20c + 5 = 5c + 65 Divide through by 5: 4c + 1 = c + 13 Subtract c from both sides: 3c + 1 = 13 Subtract 1 from both sides: 3c = 12 Divide both sides by 3: c = 4 20c + 5 = 5c …+65 20c - 5c= 65 - 5.
15c = 60.
15c/15 = 60/15.
c = 4 (alternative method).

# How do you simplify 4c-b plus b plus 5c?

That equals 9c.

# How do you factor c square plus 5c plus 6?

c 2 + 5c + 6 = (c + 2)*(c + 3)

# How do you expand 5b plus 5c in algebra?

It IS expanded.

# What is the answer for 5c plus 7 equals 23?

5c+7=23 -7 -7 5c=16 /5 /5 c= 3 & 1/5 or 16/5 thats really easy algebra 1 homework isn't it

# What is the 3 coefficient of 5c plus 7m?

5 and 7 are two coefficient. And that is all. There is no third coefficient.

# What is -5c plus d equals 2c?

It is a single equation of direct proportionality. It cannot be solved since that would require two linear equations.

Answered

# What is 3c plus 5c plus c simplified?

9c is.

Answered

In Algebra

# Which is not equivalent to the equation a - 3b 5c 9?

The expression given can't be considered to be an equation because it doesn't have an equality sign.

Answered

In Uncategorized

# How do you factor c square minus 5c plus 6?

(c - 2)(c - 3)

Answered

In Algebra

# What is 5c plus 7c plus 2b?

12c + 2b

Answered

In Algebra

# What is the answer of 5c plus 4b - c - 2b?

The simplified answer is: 4c+2b